Development of Android-Based Mathematics Learning Media on Three Dimensional Subject Materials - Hawu, Alfa Teni; Nggaba, Mayun Erawati; Randjawali, Erwin (Universitas Wiralodra, 2023)
This study aims to develop learning media products in the form of an android application called Geometry Learning to help students understand the concept of three dimensions. This research is included in the Research and Development (R&D) type using the ADDIE research development model (Analysis, Design, Development, Implementation, and Evaluation). The development of this research is based on several assessments of the developed Android-based learning media. The assessment results given by material experts have an average percentage of 87% (very feasible), and the assessment given by media experts has an average percentage of 91% (very feasible). In addition, the students were also assessed with an average percentage of 96.6% (very decent), and the average percentage of the teacher's assessment was 81% (very decent). Thus, the application of learning media in the form of an android application is feasible to be used in the learning process.